2018
DOI: 10.1002/humu.23684
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of predisposing epimutation in retinoblastoma

Abstract: Retinoblastoma (RB), which represents the most common childhood eye cancer, is caused by biallelic inactivation of RB1 gene. Promoter hypermethylation is quite frequent in RB tissues but conclusive evidence of soma‐wide predisposing epimutations is currently scant. Here, 50 patients who tested negative for RB1 germline sequence alterations were screened for aberrant promoter methylation using methylation‐specific MLPA. The assay, performed on blood, identified a sporadic patient with methylation of CpG106, abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…The authors concluded that both genetic mutation and epimutation contributed to the retinoblastoma in this family. A rare epimutation in the RB1 gene was also identified from another recent study (38). The authors showed that germline DNA methylation was associated with silencing of the RB1 gene expression.…”
Section: Understanding Cancer From the Perspective Of Epigenetic Regusupporting
confidence: 52%
“…The authors concluded that both genetic mutation and epimutation contributed to the retinoblastoma in this family. A rare epimutation in the RB1 gene was also identified from another recent study (38). The authors showed that germline DNA methylation was associated with silencing of the RB1 gene expression.…”
Section: Understanding Cancer From the Perspective Of Epigenetic Regusupporting
confidence: 52%
“…Although it is well known that methylation of the RB1 promoter is a rather frequent inactivating event in retinoblastoma cancer cells, the role of constitutive epimutations has been poorly investigated and it has long been controversial [120][121][122]. However, a recent study demonstrated that RB1 promoter methylation can act as the first 'hit' in rare cases of retinoblastoma [123]. The presence of mosaic promoter methylation segregating with the disease was demonstrated by MS-MLPA in the blood of one out of 50 retinoblastoma patients who tested negative for germline predisposing variants.…”
Section: Retinoblastomamentioning
confidence: 99%
“…For example, Lynch syndrome typically is caused by point mutations or deletions or duplications in one of the mismatch repair genes; however, both constitutional and mosaic epimutations in the promoters of MLH1 and MSH2 also have been reported 5‐7 . Constitutional promoter methylation of the RB1 gene has been documented in a child with unilateral retinoblastoma 8 . Mosaic epimutations of SDHC have been observed in patients with gastrointestinal stromal tumors 9 .…”
Section: Introductionmentioning
confidence: 99%